Changed Resting-State Brain Signal in Parkinson's Patients With Mild Depression - Wang, Min; Liao, Haiyan; Shen, Qin; Cai, Sainan; Zhang, Hongchun; Xiang, Yijuan; Liu, Siyu; Wang, Tianyu; Zi, Yuheng; Mao, Zhenni; Tan, Changlian (Frontiers in Neurology, 2020)
Background: Depression is reported to occur 5–10 years early than the onset of motor symptoms in Parkinson (PD) patients. However, markers for early diagnosis of PD in individuals with sub-clinical depression still remain to be identified. Purpose: This study utilized Regional Homogeneity (ReHo) to investigate the alterations in resting state brain activities in Parkinson (PD) patients with different degrees of depression. Methods: Twenty non-depressed PD patients, twenty mild to moderately depressed PD patients, and thirteen severely depressed PD patients were recruited. Hamilton Depression Scale (HDS) and the Beck Depression Inventory (BDI) were assessed depression. Resting-state functional magnetic resonance imaging (rs-MRI) was analyzed with ReHo. Results: PD patients with mild to moderate depression had decreased ReHo in the left dorsal anterior cingulate cortex when compared with PD patients without depression. PD patients with severe depression exhibited increased ReHo in the left inferior prefrontal gyrus and right orbitofrontal area when compared with PD patients with mild to moderate depression. ReHo values in the bilateral supplementary motor area (SMA) in PD patients with severe depression was also increased when compared with PD patients without depression. Conclusions: This study suggests that rs-MRI with ReHo analysis can detect early changes in brain function that associate with depression in PD patients, which could be biomarkers for early diagnosis and treatment of PD related depression.